Nazi wireless propaganda : Lord Haw-Haw and British public opinion in the second World War - M. A. Doherty. (Edinburgh University Press)
Includes bibliographical references (p. [193]-198) and index. "A CD of 24 German wartime broadcasts to Britain accompanies this book."